On the dependence of effective mechanical properties of ceramics on partial concentrations of different size pores in its structure; AIP Conference Proceedings; Vol. 1623 : International Conference on Physical Mesomechanics of Multilevel Systems 2014, Tomsk, Russia, 3–5 September 2014 - Konovalenko I. S. Igor Sergeevich; Smolin A. Yu. Alexey Yurievich; Konovalenko I. S. Ivan Sergeevich; Promakhov V. V. Vladimir; Psakhie S. G. Sergey Grigorievich (2014, 2014)
Title screen